PENERAPAN NEW PUBLIC MANAGEMENT (NPM) DI INDONESIA; Reformasi Birokrasi, Desentralisasi, Kerjasama Pemerintah dan Swasta Dalam Meningkatkan Pelayanan Publik - PUSPAWATI, ANI AGUS (PUBLISIA (Jurnal Ilmu Administrasi Publik), 2016)
New Public management (NPM) is a new paradigm in public sector management. And was first developed in the 1980s, especially in New Zealand, the UK and the U.S. as a result of the emergence of welfare state crisis. This paper aims to look at how the application of NPM in Indonesia, particularly in the form of bureaucratic reform through decentralization and relationship between the government (public) and private, to improve public services.